Signing their lives away : the fame and misfortune of the men who signed the Declaration of Independence - Kiernan, Denise (Quirk Book, 2009)
Introduces readers to the lives of the fifty-six men who signed the Declaration of Independence, describing who they were, their professions, and how their lives changed in the years that followed.